Digital Tax Compliance: The Role of Literacy, Ease, and Trust - Putri Serly Audia; Heru Tjaraka; Anak Agung Gde Satia Utama (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the influence of digital tax literacy, perceived ease of use, and trust in the digital tax system on taxpayer compliance among individual taxpayers in Yogyakarta, Indonesia. Research Method: A quantitative approach was employed using purposive sampling. Data were collected from 100 individual taxpayers utilizing e-Filing, e-Billing, and DGT Online. The questionnaire was measured on a 5-point Likert scale and analyzed using multiple linear regression, with validity and reliability assessments and classical assumption testing. Results and Discussion: The findings reveal that digital tax literacy, perceived ease of use, and trust in the digital tax system have significant positive effects on taxpayer compliance. Perceived ease of use showed the strongest effect (β = 0.459; p < 0.001), followed by trust (β = 0.436; p < 0.001) and digital tax literacy (β = 0.049; p = 0.030). The model produced an adjusted R² of 0.920. Implications: The study highlights the importance of improving digital literacy, system usability, and public trust to strengthen voluntary taxpayer compliance. Originality: This study integrates TAM and TPB in the context of Indonesia’s digital taxation.